Optimization, scale-up and characterization of sesquiterpene from oil palm frond juice - Mohd Zahari, Mior Ahmad Khushairi; Saiful Nizam, Tajuddin; Aizi Nor Mazila, Ramli; Nina Suhaity, Azmi (2017)
Fungi produce various mixtures of gas-phase, carbon-based compounds called volatile organic compounds (VOCs) that due to their small size can diffuse through the atmosphere and soils. VOCs are carbon-based solids and liquids that readily enter the gas phase by vaporizing at 0.01 kPa at a temperature of approximately 20 °C. Ceratocystis fimbriata is a fungus which has the potential for synthesizing esters, it grows quickly and produces a variety of aromas (peach, pineapple, banana, citrus and rose) depending on the strain and culture conditions was using in this study. The aim of this study to screen and optimize methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate using a series of experimental design by a head space-solid phase micro extraction (HS-SPME) technique combined with gas chromatography-mass spectroscopy (GC–MS) was used to separate the relative peak area of the compound during the fermentation. Optimization of production of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate are affected by several factors during the period of fermentation. Series of experimental designs were applied to screen and optimize the production of the compound. In screening 24 full factorial design were used to find significant factors affecting production of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, which are incubation temperature (°C), initial pH medium, agitation speed (rpm) and concentration of glucose (g/L) in OPF juice. The responses in screening were fitted with a multiple linear regression equation and obtained a correlation (R² = 0. 0.8960) between the experimental data and model data. Then central composite design (CCD) was applied as the experimental design and a polynomial regression model with quadratic term was used to analyze the experimental data using analysis of variance (ANOVA). ANOVA analysis showed that the model was very significant (p < 0.0001) for the methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production. The responses were fitted with the second order polynomial equation with high correlation (R² = 0.9598) between the observed and predicted values. The results of optimization process showed that a maximum methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production was obtained under the condition of initial pH medium (8), agitation speed (100 rpm) and incubation temperature (25°C). Under these optimized conditions, the highest 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production was found to be when the retention time was 32.80 minutes and the relative peak area was 0.25 % of chromatogram area by using GC-SPME. This study will provide good guideline to produce methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate compound using OPF juice as sole substrate by Ceratocystis fimbriata.